Ecotoxicological and human health risk assessment of triclosan antibacterial agent from municipal wastewater treatment plants - Afshin Ebrahimi; Karim Ebrahimpour; Farzaneh Mohammadi; Malihe Moazeni (IWA Publishing, 2024)
In this study, the occurrence and environmental risks related to triclosan (TCS) in the two wastewater treatment plants (WWTPs) were investigated in Isfahan, Iran. Influent and effluent samples were collected and analyzed by dispersive liquid-liquid microextraction (DLLME)-GC-MS method with derivatization. Moreover, the risk of TCS exposure was conducted for aquatic organisms (algae, crustaceans, and fishes) and humans (males and females). TCS mean concentrations in influent and effluent of WWTPs were in the range of 3.70-52.99 and 0.83-1.09 μg/L, respectively. There were also no differences in the quantity of TCS and physicochemical parameters among the two WWTPs. The mean risk quotient (RQ) for TCS was higher than 1 (in algae) with dilution factors (DFs) equal to 1 in WWTP1. Moreover, the RQ value was higher than 1 for humans based on the reference dose of MDH (RFDMDH) in WWTP1. Furthermore, TCS concentration in wastewater effluent was the influential factor in varying the risk of TCS exposure. The results of the present study showed the risk of TCS exposure from the discharge of effluent of WWTP1 was higher than WWTP2. Moreover, the results of this study may be suitable for promoting WWTP processes to completely remove micropollutants. HIGHLIGHTS WWTP1 was at risk of TCS exposure for aquatic and human life.; Algae was highly vulnerable to TCS exposure among aquatic organisms.; The concentration of TCS was the significant effective factor in the risk of TCS.;